Preparation of terminal blend/ grafting activated crumb rubber composite modified asphalt based on response surface methodology - Xie, Juan; Zhao, Xucheng; Zhang, Yongning; Yu, Fan; Luo, Haochen; Chen, Xueru; He, Wen (Frontiers in Materials, 2023)
Recycling waste tires, crushing them into crumb rubber (CR) and adding them to asphalt can effectively improve the performance and prolong the service life of asphalt pavement. However, the crumb rubber modified asphalt (CRMA) prepared by aforementioned process is prone to segregation during storage and transportation. The terminal blend rubber asphalt (TB) prepared with fine rubber powder by high-speed shearing at high temperature for long time, which effectively improves the storage stability and working performance of CRMA, but reduces the high-temperature performance. In this study, grafting activated crumb rubber (GACR) was incorporated into TB to improve its high temperature performance without impairing storage stability. Using shearing temperature, shearing time and GACR content as influencing factors, the response surface method (RSM) was carried out to optimize the preparation process. The results indicated that 180℃ was a critical temperature, and the swelling of crumb rubber dominated with the temperature below it, but the desulfurization prevailed with the temperature above it. The extension of time favored the swelling of crumb rubber at low temperature but promoted desulfurization at high temperature. With the increase of crumb rubber content, the high temperature performance of modified asphalt improved whereas the storage stability deteriorated. According to the determination of response values and the prediction of optimal values, the suitable preparation conditions and parameters were recommended as shearing temperature of 190℃, shearing time of 90 min, and GACR content of 15%. The composite modified asphalt prepared through the optimized process showed good high temperature stability and storage stability.